Alternative Measures of Well-Being - Boarini, Romina (OECD Economics Department Working Papers, 2006)
This paper assesses if GDP per capita is an adequate proxy as a measure of wellbeing or whether other indicators are more suitable for this purpose. Within the national accounts framework, other better measures of economic resources exist, but they are closely correlated with GDP per capita and are not as readily available. Illustrative calculations to ?extend? measures of economic resources to include leisure time, the sharing of income within households and distributional concerns suggest that cross-country ranking of based on these indicators and GDP per capita are generally similar, although they have evolved differently over time. Across OECD countries, levels of most measures of specific social conditions are significantly related to GDP per capita while changes over time are not. However, survey based data on happiness and life-satisfaction across OECD countries are only weakly related to levels of GDP per capita. Overall, measures of GDP per capita and economic growth remain critical for any assessment of wellbeing but they need to be complemented with measures of other dimensions of well-being to get a comprehensive picture of well-being